PENGARUH MOTIVASI, KOMUNIKASI, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA CV POLOWIJO KEDIRI - Bramanta, Valen Rengga; Sumantri, Bambang Agus; Leksono, Poniran Yudho (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
The amount of competition between companies, both companies engaged in services and in the field of products, is a common thing, especially lately. Each company has its own way of providing the best for its customers. The approach in this study uses a causal approach. Data collection by means of questionnaires distributed to employees. The population in this study were all employees of CV Polowijo Kediri. The sample used was 40 people. The data analysis technique used multiple linear analysis. This study concludes that the variables of motivation, communication, and work environment have a simultaneous and partial effect on employee performance at CV Polowijo Kediri.